Peningkatan Pengetahuan Masyarakat terhadap Penggunaan Obat Batuk Tradisional - Putri Ayu Trininda Imran; Akbar Asfar; Haeril Amir (Window of Nursing Journal, 2025)
Coughing is caused by smoking, exposure to cigarette smoke, and polluted environments. One cough treatment is non-pharmacological therapy using traditional medicine. According to the World Health Organization (WHO), herbal medicine is used by up to 65% of the population in developed countries and 80% in developing countries. One area in Indonesia that still uses traditional medicine is Central Buton, Southeast Sulawesi. Knowledge is the result of knowing what has happened after someone feels an object. Without knowledge, a person has no basis for making decisions and determining actions to deal with problems. The purpose of this study was to determine the relationship between community knowledge and the use of traditional cough medicine in Mawasangka Village, Central Buton Regency. This study was a quantitative analytical study with a Cross Sectional design. The population of this study was all residents of Mawasangka Village who met the inclusion criteria, namely people who are currently or have consumed traditional cough medicine and are aged ≥17 years - 65 years. The sample determination used the Slovin formula with a Purposive Sampling technique and obtained 98 respondents. Data collection used a research instrument in the form of a questionnaire that has been tested for validity and reliability.  The data analysis used was univariate and bivariate, bivariate using logistic regression test with a significance level of α = 0.05. The results showed that from 98 respondents, 24.5% of the community had good knowledge, 67.3% had sufficient knowledge, and 8.2% had insufficient knowledge. The results of the logistic regression test obtained a knowledge value of p = 0.322 meaning the p value> 0.05. In conclusion, there is no relationship between community knowledge and the use of traditional cough medicine in Mawasangka Village, Central Buton Regency. The use of traditional cough medicine is not always related to a person's level of knowledge because many other factors are more dominant.